GE_GERICHTE C/26350/2015 vom 25. April 2016 - GE Cour de justice (2016)
BAIL À LOYER; CONCLUSION DU CONTRAT; CAS CLAIR; RÉSILIATION; EXPULSION DE LOCATAIRE; EXÉCUTION(PROCÉDURE) | CPC.317.1; CPC.257; CO.257d; CO.266l; OBLF.9.1; CO.1.2; CPC.236.3